THE IMPACT OF ADMINISTERING CINNAMON INFUSIONS ON LOWERING BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS PATIENTS IN THE SERVICE AREA OF KUTA BARO HEALTH CENTER, ACEH BESAR DISTRICT - Desreza, Nanda; Raiyani, Maulida (Transpublika Publisher, 2023)
Diabetes mellitus is a chronic disease characterized by elevated blood glucose levels and often accompanied by complications. Complications that occur in diabetes mellitus patients include blurred vision, cataracts, diabetic retinopathy, kidney damage, frequent loss of pain sensation, potential gangrene formation, and amputation to prevent the spread of gangrene to other tissues. The management of diabetes mellitus can be done pharmacologically through the administration of anti-diabetes medications, insulin injections, and non-pharmacological approaches such as cinnamon tea infusion. The research objective is to determine the effect of cinnamon tea infusion on reducing blood sugar levels in diabetes mellitus patients in the Kuta Baro Primary Health Center, Aceh Besar District in 2023. This research used a quasi-experimental design with a sample size of 20 diabetes mellitus patients, selected through purposive sampling. The study was conducted from December 28, 2022, to January 5, 2023, and data analysis included univariate and bivariate analysis. The results showed that before the administration of cinnamon tea infusion, the average blood sugar level was 255.80, while after the administration of cinnamon tea infusion, the average level was 193.05, with an average decrease in blood sugar levels of 41.33. This indicates a significant difference in blood sugar levels before and after the administration of cinnamon tea infusion with a p-value of 0.001, suggesting that cinnamon tea infusion has an effect on blood sugar levels. It is expected that healthcare professionals will improve healthcare services and promote the use of cinnamon tea infusion among the community, especially diabetes mellitus patients.